(untitled) (Research, Society and Development, 2024)
The life expectancy of the Brazilian population has been increasing over the years, which has led to a demand for the emergence of caregivers, whether formal or informal. Formal caregivers are considered workers who have been trained for this role and are remunerated for it. Informal caregivers, for the most part, are family members who assume the role of caring for a bedridden family member when needed. When it comes to bedridden patients, the main concern is usually related to the patient’s health, often overlooking the physical and psychological aspects that lead to the burden on informal caregivers. Such burden brings suffering to the caregiver, as it restricts their personal life, affecting their emotional and professional relationships, and reducing their social support network. This stressful routine directly interferes with the caregiver’s condition and quality of life, often sacrificing their own well-being for the bedridden patient. The objective of this study is to identify and evaluate the burden on caregivers of bedridden patients in the micro area of UBS Sebastião Amorim and propose strategies to improve their quality of life.